Financial Inclusion, Human Resource Competency, and E-Commerce Adoption on MSME Financial Performance Evidence from Muslim MSMEs in Jepara Regency - FARIDHATUN FAIDAH; Diah Ayu Susanti; Indah Puspita Maharani; Widi Savitri Andriasari; Ahmad Nilnal Munachifdlil'Ula (JURNAL ECONOMINA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic growth, job creation, and income distribution. However, their increasing number is not always matched by improved financial performance. This study examines the effects of financial inclusion, human resource competency, and e-commerce adoption on the financial performance of Muslim MSMEs in Jepara, Indonesia. Using a quantitative approach with 140 respondents and multiple linear regression analysis, the results show that all variables have a positive and significant impact. Collectively, they explain a substantial variation in performance. The findings highlight the importance of financial access, skill enhancement, and digital adoption in strengthening MSME competitiveness and sustainability.